DIGITALISASI UMKM : UPAYA PENINGKATAN USAHA MIKRO KECIL MENENGAH DESA WINDUSARI - Restuning, Restuning Amalia (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2024)
In the industrial era 5.0, technology is developing rapidly throughout all levels of society. The benefits of technology can already be felt in everyday life. Such as the activities of Micro, Small and Medium Enterprises (MSMEs), in running their businesses they have digitized by marketing online. The aim of this research is to examine further the impact of digital marketing on increasing the sales volume of MSMEs in Windusari Village. The analysis used is descriptive qualitative using a triangulation model, namely a mixed method of interviewing and observing MSMEs actors. The results of this research indicate that digital marketing has not been fully utilized optimally by MSMEs in Windusari Village. This is because most of the business actors in Windusari Village are elderly mothers for whom technology has not been well absorbed. Even though its use is not yet optimal, digital marketing can make it easier for MSMEs to provide information and interact directly with consumers, expand market share and increase sales volume for MSMEs in Windusari Village.